2005
DOI: 10.1590/s0101-81752005000400031
|View full text |Cite
|
Sign up to set email alerts
|

Trap-nesting bees (Hymenoptera, Apoidea) in areas of dry semideciduous forest and caatinga, Bahia, Brazil

Abstract: ABSTRACT. In this study were examined the species richness and seasonal abundance of cavity-nesting bees in areas of dry semi-deciduous forest and caatinga in the State of Bahia, Brazil. Sampling was done employing two types of trap-nests: bamboo canes and tubes made of black cardboard with dimensions of either 58 x 6 mm or 105 x 8 mm. The traps were inspected once a month. One hundred and forty-six nests of 11 bee species were collected in the forest, and 121 nests of seven species were collected in the caati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
5
16
0
8
Order By: Relevance
“…Among the parasitoid species that may attack the brood cells, Coelioxys spp., M. australica (Eulophidae), and the cuckoo wasp, Chrysis spp., are known to parasitize nests of Megachile and other bee species (e.g., Michener 1953;Zillikens and Steiner 2004;Pitts-Singer and Cane 2011;Filho and Garófalo 2016). Brood parasitism of leafcutting bees by species of Coelioxys is well documented worldwide, including Brazil (Krombein 1967;Michener 2000;Scott et al 2000;Aguiar et al 2005;Cardoso and Silveira 2012), supporting our findings. The overall rate of parasitism was 20.7%, similar for trap nesting Hymenoptera in tropical and subtropical regions (between 10 and 20%; e.g., Paini 2004;Torretta et al 2012;Alvarez et al 2016) with some notable exceptions (e.g., 49% in O' Neill and O'Neill 2016, 76.9% in Filho and Garófalo 2016, and only 3% in Staab et al 2014.…”
Section: Discussionsupporting
confidence: 87%
“…Among the parasitoid species that may attack the brood cells, Coelioxys spp., M. australica (Eulophidae), and the cuckoo wasp, Chrysis spp., are known to parasitize nests of Megachile and other bee species (e.g., Michener 1953;Zillikens and Steiner 2004;Pitts-Singer and Cane 2011;Filho and Garófalo 2016). Brood parasitism of leafcutting bees by species of Coelioxys is well documented worldwide, including Brazil (Krombein 1967;Michener 2000;Scott et al 2000;Aguiar et al 2005;Cardoso and Silveira 2012), supporting our findings. The overall rate of parasitism was 20.7%, similar for trap nesting Hymenoptera in tropical and subtropical regions (between 10 and 20%; e.g., Paini 2004;Torretta et al 2012;Alvarez et al 2016) with some notable exceptions (e.g., 49% in O' Neill and O'Neill 2016, 76.9% in Filho and Garófalo 2016, and only 3% in Staab et al 2014.…”
Section: Discussionsupporting
confidence: 87%
“…A slight preference for cardboard tubes was also verif ied by Aguiar et al (2005) and Nascimento & Garófalo (2010), but these authors found also nests of this species in bamboo canes. Thus, the type of material used for trap-nests can be suggested as an influential factor in the choice of nesting cavity.…”
Section: Discussionmentioning
confidence: 52%
“…Desse total cerca de 20% dos ninhos foram fundados por abelhas e o restante (80%) por vespas. Segundo Garófalo et al (2004) membros das famílias Apidae e Megachilidae têm sido freqüentemente capturados com essa metodologia no Brasil, embora em outros trabalhos apenas abelhas da família Apidae tenham sido capturadas (Viana et al 2001, Aguiar et al 2005.…”
Section: Iscas De Cheirounclassified